Development of the ETA 020 Freshman Seminar Course - Kinsler, Les; Leite, Pedro; Williamson, Matt (My University, 2010)
Research has shown that the freshman year can be crucial for the success or failure of first year students. The first-year experience for undergraduate students has been a topic of concern in our College for some time now - specially when it relates to student success, satisfaction, and retention. Our students come from diverse backgrounds, different levels of academic preparation, age levels, and socio-economic backgrounds. Some are not even sure if they are in the right place to start with. These factors can make the transition to post-secondary education very difficult for most students, specially the freshman class. This paper discusses the evolution of the Freshman Seminar course (ETA 020) from inception to its current configuration. Topics include the events and forces driving the format and topic changes of the course, outcome expectations by faculty, students' course evaluation, and plans for expected changes.
Keywords: Engineering technology education; First year experience; Retention